Videoactivismo y apropiación de las tecnologías. El caso de 15m.cc. - MONTERO, David; SIERRA CABALLERO, Francisco (Chasqui (13901079))
The emergence of a wave of citizen protest since 2011 has foreshadowed the advent of different subjectivities largely defined by innovative cultural dynamics and by the use of the Internet as a source of emancipation. This text engages critically with the relationship between social appropriation patterns on the Internet and the emergence of a new actor-network as defined by these initiatives. The social and cultural context which sustains the analysis points towards video-activism in the "indignados" movement in Spain and, specifically, to the case of 15m.cc as an emancipatory exercise which revolves around three main points: re-collectivization of social action on-line, individual positioning in relation to the so-called "voice of the crowd" and the use of anonymity and transparency.